Neutrophil-to-Lymphocyte Ratio Facilitates Identification of Obstructive Sleep Apnea in Patients with Type B Aortic Dissection. (30th November 2021) - Jiang, Dandan; Chen, Qu; Su, Weiming; Wu, Dinghui
Abstract : Purpose . To determine whether the neutrophil-to-lymphocyte ratio (NLR) aids in the detection of obstructive sleep apnea (OSA) in patients with type B aortic dissection (TBAD). Methods . 324 patients with TBAD or type B aortic intramural hematoma (TB-AIMH) underwent an overnight sleep study. We divided the eligible 256 studied subjects into three groups: group A ( n = 109, TBAD patients with OSA), group B ( n = 68, TB-AIMH patients with OSA), and group C ( n = 79, TBAD patients without OSA). Baseline characteristics, biochemical and sleep parameters, and STOP-Bang questionnaire scores were collected. To assess the predictive efficacy of potential variables, multivariate logistic regression analysis and receiver operating characteristic (ROC) curves were used. Results . The study found that about 58% of TBAD patients and 54% of TB-AIMH patients had OSA, a majority of whom had moderate to severe OSA (95.41% and 89.71%, respectively). In the comparison of sleep parameters between patients with TBAD and TB-AIMH, no other than apnea and hypopnea index (AHI) made a significant difference. The multivariate logistic regression analysis showed that neutrophil-to-lymphocyte ratio (NLR) (odds ratio (OR): 3.614, 95% confidence interval (CI): 2.273–5.748, and P < 0.05 ) and STOP-Bang scores (OR: 1.97, 95% CI: 1.34–2.90, and P < 0.05 ) were both independent predictors for OSA in patients with TBAD. ROC curves showed NLR had higher sensitivity (65% versus 59%) and specificity (86% versus 57%) for OSA than the STOP-Bang questionnaire. Furthermore, NLR was positively correlated with AHI through the Spearman test ( r = 0.398 and P < 0.05 ). Conclusion . NLR was an independent predictor of OSA in TBAD patients with higher sensitivity and specificity than the STOP-Bang questionnaire, and it was positively associated with AHI. NLR may aid in the diagnosis and risk stratification of OSA in TBAD patients.